Bureaucracy Reformation: Open Government Partnership as a change strategy in Bojonegoro regency - Fikri, Haidar; Suharto, Didik G; Nugroho, Rino Ardhian (FIA UB, 2018)
A complicated and rigid public service is a characteristic of bureaucracy.Besides that, public service that is not transparent and accountable will create a bureaucracy as an ineffective and inefficient organization. It will raise corruption, mal-administration, and service discrimination to the society. Government of Bojonegoro regency as society servant has own strategy to solve that problem. Open Government Partnership becomes a strategy implemented by bureaucracy in Bojonegoro regency. It is because this strategy has not been implemented yet. This research is aimed to know how Bojonegoro’s bureaucracy solves the problem by using Open Government Partnership in the context of public service. This research uses an approach of electronic government and bureaucracy reformation. A qualitative-descriptive method is used in this research as a data analysis in the field. The process of collecting data is supported by observation, literature review, interview, and documentation. The result of this research is strategy of Open Government Partnership using variables such as; transparency, participation and collaboration to create a successful bureaucracy reformation. Transparency also becomes an essential value on each service and policy implementation because the government involves the society to decide a case. The government conducts some collaboration in order that all society elements can work together with them to realize bureaucracy in Bojonegoro regency.Strategy of Open Governement Partnership takes Bojonegoro regency to represent Indonesia in the event of innovation promotion of OGP in the international level.